2015
DOI: 10.1037/mil0000069
|View full text |Cite
|
Sign up to set email alerts
|

On the Stability of Psychological Hardiness: A Three-Year Longitudinal Study

Abstract: This file was dowloaded from the institutional repository Brage NIH -brage.bibsys.no/nih Hystad, S. W., Olsen, O. K., Espevik, R., Säfvenbom, R. (2015). On the stability of psychological hardiness: a three-year longitudinal study.Military Psychology, 27,[155][156][157][158][159][160][161][162][163][164][165][166][167][168].Dette er siste tekst-versjon av artikkelen, og den kan inneholde små forskjeller fra forlagets pdf-versjon. Forlagets pdf-versjon finner du på www.apa.org: http://dx.doi.org/10.1037/mil00000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 34 publications
0
19
0
1
Order By: Relevance
“…It is also the case that hardiness and avoidance coping were measured at the same time point in both samples, whereas ideally, avoidance coping should be measured after hardiness in order to demonstrate a clear causal sequence. But given that hardiness is a relatively stable personality trait as compared with coping strategies that are more changeable, it seems unlikely that avoidance coping actions would cause hardiness levels to decline (Hystad, Olsen, Espevik & Säfvenbom, ).…”
Section: Discussionmentioning
confidence: 99%
“…It is also the case that hardiness and avoidance coping were measured at the same time point in both samples, whereas ideally, avoidance coping should be measured after hardiness in order to demonstrate a clear causal sequence. But given that hardiness is a relatively stable personality trait as compared with coping strategies that are more changeable, it seems unlikely that avoidance coping actions would cause hardiness levels to decline (Hystad, Olsen, Espevik & Säfvenbom, ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, although psychological resilience is often at the conceptual core of stress management, it remains questionable whether this is an effective choice when aiming to improve the ability of the police work force, or similar professions like the military to deal with stressful situations. A recent study by Hystad et al (2015) stressed group level stability of hardiness, a concept akin to psychological resilience, after 3 years of military training and thereby disputing the changeability of psychological resilience within the military population. In contrast, the study by McCraty et al (2009) did find positive training effects, but focused more on other aspects such as coping, motivation, and/or positive outlook.…”
Section: Discussionmentioning
confidence: 99%
“…Particular attention is drawn to the studies of hardiness formation in the process of professional development in law enforcement body employees. S. W. Hystad and others found no statistically significant effect of time on hardiness scores in students from 3 different Norwegian military academies [13]. The results of the study conducted by E. A. Kuasheva showed that the dynamics of hardiness in the process of professionalization is nonlinear and reaches maximum values in the second and final stages of service in the lawenforcement bodies [14].…”
Section: Problem Statementmentioning
confidence: 99%